Esophageal perforation: A rare but fatal complication of urgent sengstaken blakemore tube intubation [Özofagus perforasyonu: Acil sengstaken blakemore tüp kullani{dotless}mi{dotless} sonrasi{dotless} gelişen nadir fakat ölümcül komplikasyon] - BİLGİN, HÜSEYİN; ÇİMŞİT, NURİ ÇAGATAY; ÖZDOĞAN, OSMAN CAVİT; KARAKURT, SAİT (Turkish Society of Medical and Surgical Intensive Care Medicine, 2014)
Acute variceal bleeding is an important cause of mortality among cirrhotic patients. Endoscopic band ligation and medical vasoactive drugs are the main treatment options for actively bleeding varices. In some cases, these therapies can fail and a Sen-gstaken Blakemore tube (SBT) is used to stop the bleeding by direct compression of varices. Although it is very effective in stopping variceal bleeding, SBT has some lethal complications. In this paper, we discuss the case of a patient who developed esopha-geal perforation after insertion of the SBT.
Keywords: Balloon tamponade; Mediastinitis; Variceal bleeding